(untitled) (Aporte Santiaguino, 2019)
The objective of this studywas to identify the sustainable alternatives for crop residues management, implemented by avocado (Persea americana Mill.) and tangerine (Citrus spp.) producers in Cañete, Lima, Peru. For this, 48 farms, located in the districts of San Vicente, San Luis, Quilmaná, Nuevo Imperial, Imperial and Lunahuaná, were visited. The results indicated that, the sustainable alternatives for crop residues management consisted in threshing and incorporation into the soil after pruning, mulch, the urial of discarded fruit and the use of parasitoid recovery chambers